Defining standard symbols for street network maps for urban planning based on user requirements - Sluter, C.; Brandalize, M.; Ivanova, Ivana; van Elzakker, C. (2013)
This paper describes the first step of a research project that aims to establish a standard set of symbols for the cartographic representation of urban regions. This first step is a case study that focuses on street network symbol design as part of a municipal master plan. In Brazil, the Federal Law 10.257 of 2001 demands that a municipal master plan is the basic instrument for political policies for the development of urban areas. According to the Brazilian Federal Constitution every municipality that has over 20,000 inhabitants is obliged to have a municipal master plan. In the state of Parana, Brazil, 3 groups of professionals are involved in establishing and implementing a master plan: state government technicians, municipality technicians, and urban planners. Commonly, to propose a master plan, the municipal executive government needs to contract a commercial enterprise, which is employing urban planners. Their plan proposal is then analyzed by municipality technicians and sent to the council of representatives to be approved as a set of laws. The state government technicians, who are the users we focus on in this case study, work for an institution called ParanaCidade that is responsible to provide knowledge support to municipality technicians who have to review a master plan. According to ParanaCidade a municipal master plan is developed in five stages, where three of them are directly dependent on spatial analysis. They are the analysis of the regional, municipal and urban reality; the master plan guidelines and proposal; and the draft of a set of laws. In these stages it is important that every cartographic representation of different aspects of urban reality be perfectly understood by the 3 groups of professionals. However, that is currently not the case in the state of Parana. Today, in different municipalities, urban planners use different classifications for the same phenomena, and those differences are not always based on the specifics of the geographic region. As every classification is depicted by a unique set of symbols, there are also different symbols for representing the same phenomenon. This fact can affect the efficiency of the decision making by state government and municipality technicians in the field of urban planning. Our proposed solution to this problem is a standard for map symbolization which is the result of this case study. The street network was chosen as a research starting point because its design and construction depend on most of the geographic characteristics that must be part of the analysis of the municipal reality. At the same time, the proposals for all of the other aspects of an urban plan, e.g. land use zoning and public transportation, are dependent on the street network. The user requirement analysis is executed through scientific methodology and reference is also made to research into the cartographic design of interactive land use planning maps in the Netherlands. The steps of the methodology are (1) understanding the geographic knowledge based on which users will accomplish tasks for proposing a municipal master plan, (2) defining the street network classification that can be suitable for every map scale necessary for decision making based on spatial analysis, (3) designing a proposed standard symbology for the street system network, (4) designing and implementing qualitative user tests. The tests are based on tasks related to scenarios that represent some actual situations in urban planning. Representatives of the users perform the tasks using maps designed with the proposed standard symbolization. They are also encouraged to 'think aloud' while performing the tasks. And a 'focus group' activity will be prepared based on the results of the user tests in order to improve our proposal for the standard symbolization.